Chiral Biomaterials: From Molecular Design to Regenerative Medicine. Issue 6 (19th January 2016) - Green, David W.; Lee, Jong‐Min; Kim, Eun‐Jung; Lee, Dong‐Joon; Jung, Han‐Sung
Abstract : Chirality is integral to biological complexity. Chiral biomolecules are central to all fundamental recognition, conformational and replication functions in biological systems. Chirality also exists in living cells and higher order biological structures. Less is known about the cellular interactions with chirality, although most living cells are imprinted with chiral‐based signatures. The harnessing of molecular, supramolecular, and structural chirality has been largely overlooked in biomaterials chemistry and the engineering of biological structures for regenerative medicine. Since chirality is a fundamental element of biological architecture its implementation in materials biomimicry is a necessity for mechanical, structural, and biological reasons. Take the latter, new investigations show the direct influence of biomimetic chiral patterning and chiral‐based architecture on stem cell activities and behavior. Biomimetic integration of chirality signatures into medical biomaterials provides a new capability to maximize biological function and compatibility especially for morphogenesis and regeneration. Abstract : Chiral design among biomaterials for regenerative medicine is reviewed with reference to future prospects. Chiral biomaterials are at an early stage of development, confined to promising short sequenced peptide supramolecules and biophysical surface patterns with biologically significant controls on human cell behavior. These studies lay the ground rules for the fabrication of more complex and clinically applicable chiral macrostructures.